Anti-Cancer and Anti-Inflammatory Potential of the Green Synthesized Silver Nanoparticles of the Red Sea Sponge Phyllospongia lamellosa Supported by Metabolomics Analysis and Docking Study - Areej A. Al-Khalaf; Hossam M. Hassan; Aisha M Alrajhi; Rania Ali El Hadi Mohamed; Wael N. Hozzein (MDPI AG, 2021)
Background: The Red Sea sponges have been endorsed as a plentiful source of bioactive compounds with promising anti-cancer and anti-inflammatory activities; therefore, exploring their potential as a source of anti-cancer metabolites has stimulated a growing research interest. Purpose: To investigate the anti-cancer and anti-inflammatory potential of the Red Sea sponges, in their bulk and silver nanostructure. Metabolomics analysis of the selected sponge followed by molecular docking studies, will be conducted to explore and predict the secondary metabolites that might provide its capability of inhibiting cancer. Materials and Methods: We prepared a chloroform extract (CE) and ethyl acetate extract (EE) of the Red Sea sponge Phyllospongia lamellosa synthesized silver nanoparticles. The prepared silver nanoparticles were characterized through UV-vis spectrophotometric, transmission electron microscopy (TEM), and Fourier-transform infrared spectroscopy (FTIR) analyses. Testing for their anti-cancer activities was performed against MCF-7, MDB-231, and MCF-10A cells. Anti-inflammatory activity against COX-1 and 2 was assessed. Furthermore, liquid chromatography-mass spectrometry (LC-MS)-based metabolomics analysis and molecular docking were also applied.